Serum Serine Peptidase Inhibitor Kazal-Type 1, Trypsinogens 1 to 3, and Complex of Trypsin 2 and α1-Antitrypsin in the Diagnosis of Severe Acute Pancreatitis. Issue 3 (March 2019) - Rainio, Mia; Lindström, Outi; Penttilä, Anne; Itkonen, Outi; Kemppainen, Esko; Stenman, Ulf-Håkan; Kylänpää, Leena
Abstract : Objectives: We explored prediction of severe acute pancreatitis (AP) and development of organ dysfunction (OD). Methods: Serum concentrations of serine peptidase inhibitor Kazal type 1 (SPINK1), trypsinogen 1, trypsinogen 2, and trypsinogen 3, complex between trypsin 2 and α1 -antitrypsin, serum C-reactive protein, creatinine, and pancreatic amylase were measured in 239 AP patients with disease onset within 72 hours. Results: SPINK1 distinguished most accurately patients who later developed severe AP. The area under the receiver operating characteristic curve for SPINK1 was 0.742, followed by trypsinogen 2 (0.726), complex between trypsin 2 and α1 -antitrypsin (0.657), creatinine (0.656), trypsinogen 1 (0.652), trypsinogen 3 (0.557), and C-reactive protein (0.499). With a cutoff of 166 μg/L, SPINK1 had a specificity of 93%, a sensitivity of 48%, and diagnostic odds ratio of 11.52. In multivariate logistic regression analysis, only SPINK1 was an independent predictor of severe AP among patients presenting without OD on admission ( P < 0.001). Conclusions: Plasma levels of the biomarkers and creatinine correlated with the severity of AP and development of OD. In patients presenting without OD at admission, SPINK1 was an independent marker for later development of severe AP.